A bible reading attitude scale for Filipino college students: Its implications for religious learning - Baring, Rito V. (Animo Repository, 2006)
This study examined the implications of the Bible Reading (BR) attitude scale for Filipino College students to religious learning. To realize this end, the following objectives were addressed: a. to know the College students peculiar attitude characteristics to Bible reading and, b. to examine the implications of the BR attitude scale to religious learning. Given these objectives, qualitative and quantitative research methods were employed. The survey instrument used for this research was the pre-tested Bible Reading (BR) attitude scale developed by this author consisting of 70 items classified in six unique attitude factors. The first factor had thirty-two (32) items, the second had eleven (11) while the third had nine (9); the fourth factor consisted of eight (8), the fifth had six (6), while the sixth had four (4) items. The quantitative component followed three stages of preparations: a. the administration of the validated and pre-tested BR scale to 123 college students for standardization using percentile ranking, b. the analysis of statistical results with the percentile ranking grid including comparative statistical mean and standard deviation and, c. the administration of the standardized survey to a new set of 200 student respondents for comparative statistical analysis of the results using percentile ranking grid, mean, standard deviation and correlation of variables. On the other hand, the qualitative component included a critical description and analysis of the Bible reading attitudes of College student respondents and, an examination of the implications of the dominant reading attitudes in relation to narrative theology and religious education. For the 200 respondents, the dominant factor (factor 4) suggested a connection between life spoken in the Bible and life personally experienced. Reading the Bible is an opportunity to connect with history. The weakest factor (factor 5) indicated that Bible reading is not necessarily meant to reflect upon Gods message with the community. The communal dimension to Bible reading is weak. Further examination of the factors revealed that the Bible was better appreciated as an object of faith rather than an object of study. Reading the Bible for these students is akin to listening to the sacred text being read. Reading in this sense did not refer to electronically accessing the text but referred to reading the hard copy of the Bible. No amount of convincing or friendly pressure would be needed to make them read the Bible since Bible reading is a personal task which need not be imposed or suggested. The sacred text is appreciated through a contextual encounter of the story behind the text. Their attitudes to Bible reading revealed the following characteristics: Bible reading is a proclamation of Gods works and words for historical change (Jewish history), divine intervention (Gods works), and personal growth (facts about Jesus). Bible reading is an opportunity for change and growth. Since biblical themes talk about concrete human life situations, talking about ones experience and linking it with the biblical accounts made more sense for the student. There is a connection between life spoken in the Bible and life personally experienced. Bible reading for them is a proclamation addressed to the self, not to the community. Student attitudes reflected three dynamic shifts in faith development: distinguishing realities from fantasies, cultivating a deep relationship with God, and integrating existential questions into faith. Narratives bring the Bible reader to an encounter of life within the text. The reader is encouraged to find his/her situation in life in relation to the biblical situation. These results provided a basic respondent profile towards helping students rediscover the wisdom of divine love in the Sacred Scriptures through reading or listening to scriptural readings.